2017
DOI: 10.1364/oe.25.004335
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of physical conditions for a diode-pumped cesium vapor laser

Abstract: A diode-pumped alkali laser (DPAL) is thought to provide the significant promise for construction of high-powered lasers in the future. To examine the kinetic processes of the gas-state media (cesium vapor in this study), a mathematical model is developed while the processes including normal 3-enegry-level transition, energy pooling, and ionization are taken into account in this report. The procedures of heat transfer and laser kinetics are combined together in creating the model. We systemically investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…The maximal output power of 32 W was observed at 100˚C. This result is in agreement with that of our previous study [14,15], which is relate to the saturated vapor pressure and reabsorption of stimulated radiation. In the near future, resonator optimization and power scaling of the laser system would be carried out and investigated.…”
Section: Resultssupporting
confidence: 92%
“…The maximal output power of 32 W was observed at 100˚C. This result is in agreement with that of our previous study [14,15], which is relate to the saturated vapor pressure and reabsorption of stimulated radiation. In the near future, resonator optimization and power scaling of the laser system would be carried out and investigated.…”
Section: Resultssupporting
confidence: 92%
“…As can be seen, the output power varies only marginally and is even indistinguishable when the pump power is 13 W. The pump power intensity at the beam waist is calculated to be 8.8 kW=cm 2 when the pump power is 33 W. It has been shown that the additional chemical reactions are irrelevant in this range of pump power intensities. Our results are supported by the report of An et al, 35) in which they reported that the influence of the energy pooling and photoexcitation to the output power was a maximum of 1.63% with a pump power of 200 W.…”
Section: Calculation Of the Gas-flow Dpalsupporting
confidence: 92%
“…Diode-pumped alkali lasers (DPALs) have extensively been studied due to the potential to generate high power with good beam quality in the last decade [1][2][3][4]. The DPAL is a typical three-level laser using atomic alkali (K, or Rb, or Cs) vapor as the gain medium, and DPALs based on K, Rb, and Cs vapor have been reported for many years [5,6]. For power scaling, flowing DPALs should be given the higher priority than static DPALs due to the low thermal conductivity of mixture gases including buffer gases and alkali vapor inside a vapor cell [7].…”
Section: Introductionmentioning
confidence: 99%